PROVISION OF CONSTRUCTIVE FEEDBACK BY MEANS OF INFORMATION TECHNOLOGIES IN THE PROCESS OF FOREIGN LANGUAGE COMPETENCE DEVELOPMENT OF STUDENTS OF ECONOMIC SPECIALTIES - Ольга Вікторівна Чижикова (Інформаційні технології і засоби навчання, 2021)
The article explores the importance of forming constructive academic feedback via information technologies in the process of students’ foreign language competence development. This article reports on theoretical substantiation and practical results of the experimental work on effective feedback provision in the process of students’ foreign language communication skills development in higher education. The growing role of online space in constructive feedback designing is underlined. The author analyses scientific works in Scopus and Web of Science Databases in particular on academic feedback, its basic characteristics and its role in improving students’ foreign language competence. The article highlights the importance of carefully designing feedback process in the course of learning English with the purpose to develop students’ communication and problem-solving skills, improve their practical knowledge, enrich their professionally oriented vocabulary, and enhance other students’ abilities resulting in a better FL competence. Particular attention is paid to methods, principles and conditions that enable effective feedback formation by means of information technologies. The main elements and types of constructive feedback are analyzed. The results of the experiment as well as their interpretation are offered. The participants of the experiment were 25 first-year students of 3 economic specialties learning English as a foreign language. The products of students' activities were analyzed to investigate the most effective ways of academic feedback. The participants presented their academic outcomes in the form of a short essay, a test, and projects. The experiment results showed improvement through the reduction of grammar and lexical error rates. The results showed the reduction of 4 error categories in general. The article presents the students’ responses to different types of academic feedback (direct, indirect, metalinguistic, staff-to-student, peer feedback) in the form of an online survey. The positive effect of feedback via information technologies on students’ foreign language communication skills, professional-oriented vocabulary enrichment, English grammar skills, motivation to learn foreign languages, elaboration of educational products, self-assessment and self-improvement skills was recorded at the end of the study. The results of the experiment are discussed in light of the growing use of information technologies that enable constructive feedback provision in the process of foreign language competence development. The advantages and disadvantages of academic feedback provision by using information technologies are analyzed. Recommendations for educators and students are provided on the effective feedback formation in the process of foreign language study.